Is It First the Egg or the Shrimp? – Diversity and Variation in Microbial Communities Colonizing Broods of the Vent Shrimp Rimicaris exoculata During Embryonic Development - Methou, Pierre; Hernández-Ávila, Ivan; Aube, Johanne; Cueff-Gauchard, Valérie; Gayet, Nicolas; Amand, Louis; Shillito, Bruce; Pradillon, Florence; Cambon-Bonavita, Marie-Anne (Frontiers in Microbiology, 2019)
Rimicaris exoculata is one of the most well-known and emblematic species of endemic vent fauna. Like many other species from these ecosystems, Rimicaris shrimps host important communities of chemosynthetic bacteria living in symbiosis with their host inside the cephalothorax and gut. For many of these symbiotic partners, the mode of transmission remains to be elucidated and the starting point of the symbiotic relationship is not yet defined, but could begin with the egg. In this study, we explored the proliferation of microbial communities on R. exoculata broods through embryonic development using a combination of NGS sequencing and microscopy approaches. Variations in abundance and diversity of egg microbial communities were analyzed in broods at different developmental stages and collected from mothers at two distinct vent fields on the Mid-Atlantic Ridge (TAG and Snake Pit). We also assessed the specificity of the egg microbiome by comparing communities developing on egg surfaces with those developing on the cuticle of pleopods, which are thought to be exposed to similar environmental conditions because the brood is held under the female’s abdomen. In terms of abundance, bacterial colonization clearly increases with both egg developmental stage and the position of the egg within the brood: those closest to the exterior having a higher bacterial coverage. Bacterial biomass increase also accompanies an increase of mineral precipitations and thus clearly relates to the degree of exposure to vent fluids. In terms of diversity, most bacterial lineages were found in all samples and were also those found in the cephalothorax of adults. However, significant variation occurs in the relative abundance of these lineages, most of this variation being explained by body surface (egg vs pleopod), vent field, and developmental stage. The occurrence of symbiont-related lineages of Epsilonbacteraeota, Gammaproteobacteria, Zetaproteobacteria, and Mollicutes provide a basis for discussion on both the acquisition of symbionts and the potential roles of these bacterial communities during egg development.